An ecophysiological and developmental perspective on variation in vessel diameter. (9th August 2016) - Hacke, Uwe G.; Spicer, Rachel; Schreiber, Stefan G.; Plavcová, Lenka
Abstract: Variation in xylem vessel diameter is one of the most important parameters when evaluating plant water relations. This review provides a synthesis of the ecophysiological implications of variation in lumen diameter together with a summary of our current understanding of vessel development and its endogenous regulation. We analyzed inter‐specific variation of the mean hydraulic vessel diameter ( D v ) across biomes, intra‐specific variation of D v under natural and controlled conditions, and intra‐plant variation. We found that the D v measured in young branches tends to stay below 30 µm in regions experiencing winter frost, whereas it is highly variable in the tropical rainforest. Within a plant, the widest vessels are often found in the trunk and in large roots; smaller diameters have been reported for leaves and small lateral roots. D v varies in response to environmental factors and is not only a function of plant size. Despite the wealth of data on vessel diameter variation, the regulation of diameter is poorly understood. Polar auxin transport through the vascular cambium is a key regulator linking foliar and xylem development. Limited evidence suggests that auxin transport is also a determinant of vessel diameter. The role of auxin in cell expansion and in establishing longitudinal continuity during secondary growth deserve further study. Abstract : Variation in xylem vessel diameter impacts transport efficiency, vulnerability to freezing‐induced embolism, and other aspects of plant biology. This review provides a synthesis of the ecophysiological implications of variation in lumen diameter together with a summary of our current understanding of vessel development and its endogenous regulation. Emphasis is placed on the presumed role of auxin at multiple developmental stages.